Author Correction: Clopidogrel as a donor probe and thioenol derivatives as flexible promoieties for enabling H2S biomedicine - Yaoqiu Zhu (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author Bin Geng, which was incorrectly given as Bing Geng. This has been corrected in both the PDF and HTML versions of the Article.